Social-coalitional trait is related to coping capacity with mortality threat: association with leadership and a reduced parietal response to mortality salience - Hirano, Kanan; Oba, Kentaro; Saito, Toshiki; Kawashima, Ryuta; Sugiura, Motoaki (Frontiers in Behavioral Neuroscience, 2023)
Coping with mortality threat, a psychological threat unique to humans and distinct from general emotional distress, is traditionally characterized by immediate suppression and prolonged worldview defense within the framework of the influential terror management theory (TMT). Views regarding the personality-trait concepts for this coping capacity diverge: some favor a broad definition based on general psychological attitudes (e.g., hardiness), while others prefer a narrow definition linked to interpersonal attitudes related to social coalition (e.g., attachment style and self-transcendence). Using functional MRI, we presented healthy older participants with death-related words and explored correlations between the neural responses to mortality threat and the factor scores of the Power to Live questionnaire, which measures eight resilience-related psychobehavioral traits. We observed a significant association between the factor score and a neural response only for leadership; individuals with a high leadership score exhibited reduced neural response to mortality salience in the right inferior parietal lobule. Within the TMT framework, our findings align with the concept of the immediate suppression of death-thought accessibility associated with a secure attachment style, a trait conceptually linked to leadership. These findings highlight the unique role for the narrowly defined social-coalitional trait during the immediate stage of the coping process with mortality salience, in contrast to the broadly defined resilience-related personality traits associated with a prolonged worldview defense process. The deterioration of this coping process could constitute a distinct aspect of psychopathology, separate from dysfunction in general emotion regulation.